Financial Ratios and Share Prices of JII70 Indexed Companies for the 2018-2020 Period - Ahmad Fauzan; Rindang Matoati (The Management Journal of Binaniaga, 2021)
Abstract: The sharia capital market in Indonesia has grown over the last five years. One of the members of the sharia capital market instrument is sharia shares. During the 2015-2020 period, the number of Islamic stock issuers continued to grow. The stock index is used by investors as a tool to choose stocks that suit their needs. IDX has issued three sharia stock indexes, and the most recent one is the JII70 index. A stock index is a collection of statistics about the price movement of a group of stocks that is evaluated periodically. One of the many factors that influence stock prices is the company's financial ratios. This study aims to analyze the influence of financial ratio factors such as Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO), Return on Equity (ROE) and Earning per Share (EPS) on the stock price of JII70 indexed companies. The data used is secondary data in the form of JII70 indexed company financial statements in the 2018-2020 period. The method of determining the sample using purposive sampling. This research uses panel data regression analysis method. The results of this study show a significant effect of the DER and EPS variables on stock prices, while the CR, TATO and ROE variables do not significantly affect stock prices.Keywords: Share Price, JII70, Financial Ratio, Panel Data Regression, Sharia Shares